1997
DOI: 10.1172/jci119593
|View full text |Cite
|
Sign up to set email alerts
|

A novel pathogenesis of megacolon in Ncx/Hox11L.1 deficient mice.

Abstract: The Ncx/Hox11L.1 gene, a member of the Hox11 homeobox gene family, is mainly expressed in neural crest-derived tissues. To elucidate the role of Ncx/Hox11L.1, the gene has been inactivated in embryonic stem cells by homologous recombination. The homozygous mutant mice were viable. These mice developed megacolon with enteric ganglia by age 3-5 wk. Histochemical analysis of the ganglia revealed that the enteric neurons hyperinnervated in the narrow segment of megacolon. Some of these neuronal cells degenerated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
79
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 53 publications
2
79
0
1
Order By: Relevance
“…Hox11 is a central player in controlling spleen formation, perhaps through regulating cell survival, 31,32 and the two other genes appear important for specific neuronal functions. 33,34 Interspecies conservation of the primary sequences of these proteins is observed outside the homeobox domain suggesting common important biological functions (Figure 4d). It is noteworthy that Hox11L2 appears more closely related to Hox11 than Hox11L1.…”
Section: Leukemiamentioning
confidence: 98%
“…Hox11 is a central player in controlling spleen formation, perhaps through regulating cell survival, 31,32 and the two other genes appear important for specific neuronal functions. 33,34 Interspecies conservation of the primary sequences of these proteins is observed outside the homeobox domain suggesting common important biological functions (Figure 4d). It is noteworthy that Hox11L2 appears more closely related to Hox11 than Hox11L1.…”
Section: Leukemiamentioning
confidence: 98%
“…The origin of Drg11-positive neurons and the fates of Mash1-positive precursors are also poorly understood. The Tlx family of homeobox genes contains three members, Tlx-1/Hox11, Enx/Hox11-L1/Tlx-2, and Rnx/ Hox11L2/Tlx-3 (Dube et al 1991;Hatano et al 1991;Kennedy et al 1991;Dear et al 1993Dear et al , 1995Raju et al 1993;Roberts et al 1994;Hatano et al 1997;Shirasawa et al 1997Shirasawa et al , 2000Logan et al 1998;Tang et al 1998). In the developing hindbrain and spinal cord, Rnx and Tlx-1 are initially expressed in longitudinal columns of cells, extending through the hindbrain and spinal cord ( Fig.…”
mentioning
confidence: 99%
“…Initial descriptions indicated that myenteric ganglion cell hyperplasia (submucosal ganglia were not studied) was part of the phenotype, 56,57 although this was not confirmed by another group. 58 Searches for mutations in ENDRB, HOX11L1, or other genes implicated in HSCR (eg, RET) mutations in humans with IND B yielded negative results.…”
Section: Pathogenesis Of Ind Bmentioning
confidence: 98%